ChemInform Abstract: Fully Regiocontrolled Polyarylation of Pyridine. Issue 31 (5th August 2014) - Doebelin, Christelle; Wagner, Patrick; Bihel, Frederic; Humbert, Nicolas; Kenfack, Cyril Assongo; Mely, Yves; Bourguignon, Jean‐Jacques; Schmitt, Martine
Abstract A new route for the synthesis of the first protypical pentaarylpyridine bearing five different substituents from commercially available starting material (I) is reported.